Perdas de nutrientes associadas ao escoamento e aos sedimentos erodidos em encostas sob plantio direto - Utzig, Douglas Luis (2022)
No-tillage (NT) is widely used in areas of grain crops in tropical and subtropical regions. However, crops fields under NT with low phytomass addition and without runoff control practices are highly susceptible to degradation, resulting in low infiltration rates and consequently high runoff volumes. In addition to water and sediment loss, runoff will determine the transfer of dissolved and particulate chemical elements as nutrients. These could represent an increase in the cost of production and an impact on water resources. The objective of this study was to evaluate the effect of the amount of phytomass, scarification and terracing on the loss of nutrients (NH4 + , NO3 - + NO2 - , N total, P, K, Ca e Mg) associated with runoff, suspended sediments and its determination at deposits. The study was carried out in a representative area of grain production under no tillage in the central region of Rio Grande do Sul. The hydrological monitoring of surface runoff and sediment yield monitoring were conducted for five years in two zero-order basins (~2.4 ha) and four macroplots (~0.6 ha) during natural rainfall events. The dataset includes 18 events in the catchments and 9 events in the macroplots. In the catchments the effect of terracing was tested and in the macroplots the effects of scarification and phytomass amount were tested. The results show that there is a wide variation in nutrient concentrations in both surface runoff and eroded sediments regardless of the land management tested. Nevertheless, it is clearly noted that the main mechanism of nutrient loss is controlled by surface runoff in its dissolved fraction during high magnitude events. The effects of the higher phytomass addition and, especially, the presence of the terraces affect the nutrient losses by the greater control of the surface runoff. The nutrient losses monitored indicate the high risk of contamination of surface waters by eutrophication, increased costs of water treatment for supply and the potential for water contamination with impacts on the health of the population.